Scanning electron microscope studies on the radula teeth of four species of marine gastropods from the Gulf of Mannar, India - Venkatesan, V.; Babu, A.; Rameshkumar, P. (Indian Journal of Fisheries, 2016)
In this study scanning electron microscopy (SEM) was used to elucidate the surface morphology of radula teeth of four species of marine gastropods belonging to muricids and tonnoideans from the Gulf of Mannar. The species studied were Tonna dolium (Linne, 1758), Phalium glaucum (Linne, 1758), Murex virgineus (Roding, 1798) and Rapana rapiformis (Born, 1778). The radulae of muricid gastropods were of stenoglossan type (1+R+1) while the radulae of tonnoidean gastropods were of taenioglossate type (2+1+R+1+2). Very large radula and solid teeth in all four species indicate that they are well adapted to capture of prey and showed characteristic representation of the sharp and pointed apex. The shafts of the teeth of R. rapiformis, T. dolium and M virgeneus are thickened and expanded at the base to form a butt and the basal spur as well as their marginal and central teeth are sickle shaped. Radulae of both groups are well suited for tearing and rasping. The examination of the central tooth, the lateral and marginal ones, by SEM provides further information for species differentiation.